Myanmar Monthly Food Price Report – June 2025 - Htar, May Thet; Minten, Bart; Masias, Ian (International Food Policy Research Institute, 2025)
Rice prices declined nationally, falling by almost 20 percent year-on-year, with sharp drops in Kayah and Kayin, but significant increases in Shan (East). Rice prices are lowest in secure, major rice-producing areas and highest in most conflict- and earthquake-affected regions. Export crop prices diverged, with green gram and maize increasing due to strong international demand, while black gram and pigeon pea declined year-on-year due to reduced demand in India. Animal-sourced food prices surged, led by beef (up 47 percent) and pork (up 64 percent), due to rising production and fuel costs, while fish prices rose amid strong export demand and a seasonal fishing ban. Multiple risks lie ahead, including the aftermath of the March earthquake, falling international rice prices, ongoing conflict, and uncertain monsoon season production, all of which may undermine farm income and food security.